Anti-osteoporosis Medication Use in a High Fracture-Risk Population: Contemporary Trends in Australian Residential Aged Care Facilities - Kimberly E Lind; Mikaela L Jorgensen; Leonard C Gray; Andrew Georgiou; Johanna I Westbrook (SAGE Publishing, 2019)
Osteoporotic fractures impose substantial morbidity and mortality among older adults. Undertreatment is an ongoing concern; treatment rates declined following reports of adverse effects of guideline-recommended bisphosphonates, but new antiresorptives have since become available. Our goal was to identify contemporary trends in osteoporosis treatment guideline adherence in a high fracture-risk population. We conducted a secondary data analysis using electronic health record data of adults aged ⩾65 years from 68 residential aged care facilities in Australia during 2014-2017 (n = 9094). Using medication administration data, we identified antiresorptive (bisphosphonates and denosumab) and vitamin D supplement use among residents with osteoporosis. Regression was used to evaluate temporal trends, and resident and facility characteristics associated with antiresorptive use and vitamin D use. In 2014, 34% of women and 42% of men with osteoporosis used antiresorptives; this decreased 8 percentage points by 2017. Antiresorptive use was higher among those with a history of fracture and lower in the last year of life. Denosumab use increased but did not substitute for the continued decline in bisphosphonate use. Vitamin D was consistently used by more than 60% of residents and was higher among those with fracture history. Greater attention to the treatment of osteoporosis treatment rates among this high fracture-risk population is warranted.